2019
DOI: 10.1007/s40256-019-00356-2
|View full text |Cite
|
Sign up to set email alerts
|

Educational Impact on Apixaban Adherence in Atrial Fibrillation (the AEGEAN STUDY): A Randomized Clinical Trial

Abstract: Introduction Adherence to non-vitamin-K oral anticoagulants (NOACs) may be lower than to vitamin K antagonists because NOACs do not require routine monitoring. Objective We assessed the impact of an educational program on adherence and persistence with apixaban in patients with non-valvular atrial fibrillation (NVAF). Methods Patients with NVAF eligible for NOACs with one or more stroke risk factor (prior stroke/transient ischemic attack, age ≥ 75 years, hypertension, diabetes, or symptomatic heart failure) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
(51 reference statements)
0
20
0
2
Order By: Relevance
“…In that study, significantly higher proportions of patients were appropriately prescribed OAC in the intervention group at 6-months and 1-year 98). However, the AEGEAN study looked at the effect of additional education on adherence to apixaban over 48 weeks, however failed to find an improvement 99). Patients were randomised to standard care only, or standard care plus an education package which included a selection of reminder apps and access to a virtual clinic 99).…”
Section: Patient Persistence and Adherence With Oral Anticoagulant Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, significantly higher proportions of patients were appropriately prescribed OAC in the intervention group at 6-months and 1-year 98). However, the AEGEAN study looked at the effect of additional education on adherence to apixaban over 48 weeks, however failed to find an improvement 99). Patients were randomised to standard care only, or standard care plus an education package which included a selection of reminder apps and access to a virtual clinic 99).…”
Section: Patient Persistence and Adherence With Oral Anticoagulant Thmentioning
confidence: 99%
“…However, the AEGEAN study looked at the effect of additional education on adherence to apixaban over 48 weeks, however failed to find an improvement 99). Patients were randomised to standard care only, or standard care plus an education package which included a selection of reminder apps and access to a virtual clinic 99). Both groups were followed up every 12-weeks to determine medication adherence, and at 48 weeks there was no difference between additional education and standard care (90.4% vs. 90.1%) 99).…”
Section: Patient Persistence and Adherence With Oral Anticoagulant Thmentioning
confidence: 99%
“…A retrospective analysis of primary care data in Germany reports about a persistence to apixaban after 1 year in 62.9% with apixaban and 57.5% with VKAs [ 16 ]. In the randomized AEGEAN study investigating the effect of an educational program on the adherence and persistence to apixaban therapy, adherence and persistence with apixaban therapy after 48 months was about 90% and 86%, respectively [ 17 ]. This matches favorably with our experience, in which we observed an 88% persistence to apixaban after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…34 One trial, AEGEAN showed high adherence and persistence with apixaban (90%) but did not show additional benefit from interventions to improve adherence/persistence. 35 Also, studies of NOAC use in extremes of renal function, both severe renal impairment and supra-normal renal function. The latter is pertinent given that all three Factor Xa inhibitors showed numerically more ischaemic strokes in the subgroup with CrCl >95 mL/min when compared with warfarin in their pivotal trials, although this is not apparent in real-world observational data.…”
Section: Non-vitamin K Antagonist Oral Anticoagulants and Atrial Fibrmentioning
confidence: 99%